Newsmaking criminology in Australia and New Zealand: Results from a mixed methods study of criminologists' media engagement. Issue 1 (March 2020) - Iliadis, Mary; Richards, Imogen; Wood, Mark A
'Newsmaking criminology', as described by Barak, is the process by which criminologists contribute to the generation of 'newsworthy' media content about crime and justice, often through their engagement with broadcast and other news media. While newsmaking criminological practices have been the subject of detailed practitioner testimonials and theoretical treatise, there has been scarce empirical research on newsmaking criminology, particularly in relation to countries outside of the United States and United Kingdom. To illuminate the state of play of newsmaking criminology in Australia and New Zealand, in this paper we analyse findings from 116 survey responses and nine interviews with criminologists working in universities in these two countries, which provide insight into the extent and nature of their news media engagement, and their related perceptions. Our findings indicate that most criminologists working in Australia or New Zealand have made at least one news media appearance in the past two years, and the majority of respondents view news media engagement as a professional 'duty'. Participants also identified key political, ethical, and logistical issues relevant to their news media engagement, with several expressing a view that radio and television interviewers can influence criminologists to say things that they deem 'newsworthy'.